Основные направления совершенствования законодательства о финансово-правовой ответственности в бюджетной сфере - Mikriukova E. G., Korotaeva O. A. (Научное и образовательное пространство: перспективы развития, 2015)
Article is devoted to the financial and legal responsibility in the public sector. The legal nature of responsibility for offenses in the public sector on the basis of the current legislation of the Russian Federation. The problems in the financial and legal responsibility in the public sector and attempt to find solutions to these problems.
Keywords: финансово-правовая ответственность; правонарушение; бюджетная сфера; Бюджетный кодекс Российской Федерации; Financial and legal liability offense; public sector; the Budget Code of the Russian Federation